Longitudinal Relationship Between Bullying Victimization and Depression Among Left-Behind Children: Roles of Negative Thoughts and Self-Compassion - Yan, Ru; Xie, Ruibo; Jiang, Min; Li, Jiayi; Lin, Xiuyun; Ding, Wan (Frontiers in Psychology, 2022)
Background: Left-behind children (LBC) in China have aroused widespread concern in society and the academic field because they have a high risk of psychological problems. For left-behind children, depression is the most serious problem. Bullying victimization has been evidenced as one of the most common causes of children’s depression. However, less is known about its longitudinal association and the process for how bullying victimization influences depression among left-behind children. Thus, the presentation aims to explore the mechanisms underlying by considering the roles of left-behind children’s negative thoughts and self-compassion. Methods: The 3-wave longitudinal data were collected from a sample of 605 aged 8-11 from central China. We used the Olweus bully and victimization questionnaire, the children’s automatic thoughts scale, the depression scale, and the self-compassion scale. Results: Bullying victimization positively predicted the depression level of left-behind children. Negative thoughts and self-compassion mediate the relationship between bullying victimization and depression. In the mechanism of bullying victimization on depression exists gender differences among left-behind children. Conclusions: The present study suggested the association between bullying victimization and left-behind children’s depression and revealed the internal mechanism of negative thoughts and self-compassion. These findings provide a new perspective for left-behind children’s mental health education and intervention.